Penerapan Media Audio Visual Sebagai Upaya Meningkatkan Kemampuan Berbahasa Anak Usia Dini Melalui Metode Bercerita - Riska Mayeni; Risma Wiwita; Revi Handayani; Veni Veni; Yanti Nazmai; Sefrinal Sefrinal (Journal on Education, 2024)
The problem in this research is that children's low self-confidence in telling stories is due to limited mastery of vocabulary so that children do not dare to appear in front of the class, as well as the stories in books being too long so that children are bored and unable to retell them. The aim of the research is to improve the language skills of young children through the storytelling method. This research was carried out at the Ar-Raudhah Islamic Kindergarten using PTK with the research subjects being 10 children in group A of the Ar-Raudhah Islamic Kindergarten. Data collection techniques in this research are interviews, observations and documentation using descriptive analysis techniques. Data analysis techniques by examining every aspect of research activities at the time the research was carried out and analyzed properly. Based on the results of the last research cycle I, it was found that 4 children did not understand how to tell stories, 4 children (40%) received a score of not yet developed, 4 children (40%) are starting to develop, and 2 children (20%) are developing according to expectations and no child is developing very well. On the third day of Cycle II, the children were very enthusiastic about telling stories using audio-visual media, 8 children were able to tell stories very well. 0 children (0%) received a score of Not Yet Developing, 1 child (10%) Starting to Develop, 1 child (10%) Developing as Expected and 8 children (80%) Developing Very Well. Based on research results, children's language skills through the storytelling method have increased. Using audio-visual media can attract children's attention so that it can increase children's enthusiasm for telling stories and children's mastery of vocabulary and language skills will progress.